Solve the equation -6+3×=-9


Answer 1
Answer: -6 + 3x = -9

And 6 to both sides:
3x = -3

Divide by 3 on both sides:
x = -1

Answer: x = -1

Related Questions

A store sells ice cream with assorted toppings. They charge $$$3.00 for an ice cream plus $$50 cents per ounce of toppings.How much does an ice cream cost with $$11 ounces of toppings?
The average starting salary of this year's vocational school graduates is $35,000 with a standard deviation of $5,000. Furthermore, it is known that the starting salaries are normally distributed. What are the minimum and the maximum starting salaries of the middle 95% of the graduates
Solve for XHello, my daughter needs help with Trigonometry. I was never very gifted at math, and cannot remember too much about this subject. Please Help!
The question is in the pic pls help
The probability that a person has a certain disease is 0.03. Medical diagnostic tests are available to determine whether the person actually has the disease. If the disease is actually​ present, the probability that the medical diagnostic test will give a positive result​ (indicating that the disease is​ present) is 0.92. Of the disease is not actually​ present, the probability of a positive test result​ (indicating that the disease is​ present) is 0.01. a. If the medical diagnostic test has given a positive result​ (indicating that the disease is​ present), what is the probability that the disease is actually​ present

Two angles in a triangle are equal and their sum is equal to the third angle in the triangle. What are the measures of each of the three interior angles?


A triangle is 180 if two angles equal to eachother and the other angle is these two combines the angels will be 45 45 90

If two lines do not intersect, then
they are parallel.


If it is not intersect they are not parallel

HELP PLEASE!! i’m giving 15 points for this!!


Answer:The picture did not load

Step-by-step explanation:Sorry

Find the product of the given polynomials (5x + 8 - 6x)(4 + 2x - 7)



−2x^2+ 19x−24

Step-by-step explanation:

-2 x^2 + 19 x -24
Is the answer

5. The length of similar components produced by a company are approximated by a normal distribution model with a mean of 5 cm and a standard deviation of 0.02 cm. If a component is chosen at random a) what is the probability that the length of this component is between 4.98 and 5.02 cm



the probability that  he length of this component is between 4.98 and 5.02 cm is 0.682 (68.2%)

Step-by-step explanation:

Since the random variable X= length of component chosen at random , is normally distributed, we can define the following standardized normal variable Z:

Z= (X- μ)/σ

where μ= mean of X  , σ= standard deviation of X

for a length between 4.98 cm and 5.02 cm , then

Z₁= (X₁- μ)/σ =  (4.98 cm - 5 cm)/0.02 cm = -1

Z₂= (X₂- μ)/σ = (5.02 cm - 5 cm)/0.02 cm = 1

therefore the probability that the length is between 4.98 cm and 5.02 cm is

P( 4.98 cm ≤X≤5.02 cm)=P( -1 ≤Z≤ 1) = P(Z≤1) - P(Z≤-1)

from standard normal distribution tables we find that

P( 4.98 cm ≤X≤5.02 cm) = P(Z≤1) - P(Z≤-1) = 0.841 - 0.159 = 0.682 (68.2%)

therefore the probability that  he length of this component is between 4.98 and 5.02 cm is 0.682 (68.2%)

Three friends — let’s call them X, Y , and Z — like to play pool (pocket billiards). There are some pool games that involve three players, but these people instead like to play 9-ball, which is a game between two players with the property that a tie cannot occur (there’s always a winner and a loser in any given round). Since it’s not possible for all three of these friends to play at the same time, they use a simple rule to decide who plays in the next round: loser sits down. For example, suppose that, in round 1, X and Y play; then if X wins, Y sits down and the next game is between X and Z. Question: in the long run, which two players square off against each other most often? Least often? So far what I’ve described is completely realistic, but now we need to make a (strong) simplifying assumption. In practice people get tired and/or discouraged, so the probability that (say) X beats Y in any single round is probably not constant in time, but let’s pretend it is, to get a kind of baseline analysis: let 0 < pXY < 1 be the probability that X beats Y in any given game, and define 0 < pXZ < 1 and 0 < pY Z < 1 correspondingly. Consider the stochastic process P that keeps track of



Step-by-step explanation:

(a) If the state space is taken as S = \{(XY),(XZ),(YZ)\} , the probability of transitioning from one state, say (XY) to another state, say (XZ) will be the same as the probability of Y losing out to X, because if X and Y were playing and Y loses to X, then X and Z will play in the next match. This probability is constant with time, as mentioned in the question. Hence, the probabilities of moving from one state to another are constant over time. Hence, the Markov chain is time-homogeneous.

(b) The state transition matrix will be:

P=\begin{vmatrix} 0 & p_(XY) & (1-p_(XY))\n p_(XZ)& 0& (1-p_(XZ))\n p_(YZ)&(1-p_(YZ)) & 0\end{vmatrix},

where as stated in part (b) above, the rows of the matrix state the probability of transitioning from one of the states S = \{(XY),(XZ),(YZ)\} (in that order) at time n and the columns of the matrix state the probability of transitioning to one of the states S = \{(XY),(XZ),(YZ)\} (in the same order) at time n+1.

Consider the entries in the matrix. For example, if players X and Y are playing at time n (row 1), then X beats Y with probability p_(XY), then since Y is the loser, he sits out and X plays with Z (column 2) at the next time step. Hence, P(1, 2) = p_(XY). P(1, 1) = 0 because if X and Y are playing, one of them will be a loser and thus X and Y both together will not play at the next time step. P(1, 3) = 1 - p_(XY), because if X and Y are playing, and Y beats X, the probability of which is1 - p_(XY), then Y and Z play each other at the next time step. Similarly,P(2, 1) = p_(XZ), because if X and Z are playing and X beats Z with probabilityp_(XZ), then X plays Y at the next time step.

(c) At equilibrium,

vP = v,

i.e., the steady state distribution v of the Markov Chain is such that after applying the transition probabilities (i.e., multiplying by the matrix P), we get back the same steady state distribution v. The Eigenvalues of the matrix P are found below:

:det(P-\lambda I)=0\Rightarrow \begin{vmatrix} 0-\lambda & 0.6 & 0.4\n 0.975& 0-\lambda& 0.025\n 0.95& 0.05& 0-\lambda\end{vmatrix}=0

\Rightarrow -\lambda ^3+0.9663\lambda +0.0337=0\n\Rightarrow (\lambda -1)(\lambda ^2+\lambda +0.0337)=0

The solutions are

\lambda =1,-0.0349,-0.9651. These are the eigenvalues of P.

The sum of all the rows of the matrixP-\lambda I is equal to 0 when \lambda =1.Hence, one of the eigenvectors is :

\overline{x} = \begin{bmatrix} 1\n 1\n 1 \end{bmatrix}.

The other eigenvectors can be found using Gaussian elimination:

\overline{x} = \begin{bmatrix} 1\n -0.9862\n -0.9333 \end{bmatrix}, \overline{x} = \begin{bmatrix} -0.0017\n -0.6666\n 1 \end{bmatrix}

Hence, we can write:

P = V * D * V^(-1), where

V = \begin{bmatrix} 1 & 1 & -0.0017\n 1 & -0.9862 & -0.6666 \n 1 & -0.9333 & 1 \end{bmatrix}


D = \begin{bmatrix} 1 & 0 & 0\n 0 & -0.9651 & 0 \n 0 & 0 & -0.0349 \end{bmatrix}

After n time steps, the distribution of states is:

v = v_0P^n\Rightarrow v = v_0(VDV^(-1))^n=v_0(VDV^(-1)VDV^(-1)...VDV^(-1))=v_0(VD^nV^(-1)).

Let n be very large, say n = 1000 (steady state) and let v0 = [0.333 0.333 0.333] be the initial state. then,

D^n \approx \begin{bmatrix} 1 & 0 & 0\n 0& 0 &0 \n 0 & 0 & 0 \end{bmatrix}.


v=v_0(VD^nV^(-1))=v_0(V\begin{bmatrix} 1 & 0 & 0\n 0 &0 &0 \n 0& 0 & 0 \end{bmatrix}V^(-1))=[0.491, 0.305, 0.204].

Now, it can be verified that

vP = [0.491, 0.305,0.204]P=[0.491, 0.305,0.204].